Optimization of complex treatment of infectious mononucleosis in children - A. G. Bokovoy; M. G. Vershinina; A. Yu. Medkovа; I. V. Kovalev (LLC "Diagnostics and Vaccines", 2019)
98 patients from 2 to 12 years old were observed with infectious mononucleosis (IM). Diagnosis was confirmed by the detection of M- and G-antibodies to EBV, CMV, HHV6, PCR DNA these viruses, bacteriological and blood-tests investigations. 58 patients in the complex therapy was given probiotic bifidumbacterin forte 45-90 doses a day (1-st group). The comparison group consisted of 40 patients with IM receiving symptomatic complex therapy and antibiotics (2-nd group). The observations shoved significant decreasing of length of clinical symptoms IM in the 1-st group with comparison of the 2-nd group. The investigation of concentration DNA these viruses (1-st group) demonstrated its rapid decreasing in blood to the second week of mononucleosis. The obtained results allow to recommend bifidumbacterin forte in the complex therapy in children with these infections.